PARASITES’ SPECIES DIVERSITY ANALYSIS OF SEPARATE FISH SPECIES IN FRESHWATER RESERVOIRS OF UKRAINE. PARASITIC PROTOZOA - Melnychuk, V.; Yevstafieva, V.; Khomenko, A.; Sydorenko, I. (Scientific Progress & Innovations, 2021)
Fish farming is an important and integral part of business in Ukraine, in which certain species of fish play a key role. It should be noted that anthropogenic impact of human on water objects, the current state of ecology, the growing rate of alien species populating aquatic ecosystems of Ukraine together contribute to the formation of new symbiotic relationships between fish fauna and parasitic organisms, including parasitic protozoa. The so-called “new relationships” usually lead to worsening the epizootic situation in water reservoirs, causing the emergence of mass fish diseases. As a result, the quantity and quality of fish products are reduced, which leads to economic losses. In this regard, the purpose of this review is to determine the current state of parasitic protozoa fauna of certain fish species in freshwater bodies of Ukraine. Different fish species were selected as the object of the survey – grass carp, silver carp, sand grubby, perch, crucian carp (common – golden and silver crucian carp), pike, rudd, carp and roach. These fish species are part of the fish cenosis nucleus of the vast majority of freshwater bodies of Ukraine and have a different nature of nutrition. The paper highlights data on the fauna of parasitic protozoa of these fish species. It has been established that at present the fauna of fish protozoases has 59 species belonging to 5 classes: Kinetoplastomonada (Honigberg, 1963), Coccidiomorphea (Doflein, 1901), Myxozoa (Grassé, 1970), Oligohymenophorea (de Puytorac et al., 1974) and Rinostomata (Jankowski, 1978), 14 families and 18 genera. The dominant class was Oligohymenophorea. According to scientists, the fauna of grass carp (34 species), silver carp (29 species) and crucian carp (20 species) turned out to be the richest. According to the researchers’ data, perch, pike, sand grubby and rudd are the least affected by parasitic protozoa: 2-3 species of parasitic protozoa have been recorded in them. It should be noted that among the identified parasitic protozoa of 10 species – (Costia necatrix Henneguy, 1884, Sphaerospora carassii Kudo, 1919, Myxobolus dispar Thélohan, 1895, M. ellipsoides Thélohan, 1892, Ichthyophthirius multifiliis Fouquet, 1876, Trichodina reticulata Hirschmann et Partsch, 1955, Trichodinella epizootica Raabe, 1950, Chloromyxum fluviatile Thélohan, 1892, Tripartiella bulbosa Davis, 1947 and Balantidium ctenopharyngodoni Chen, 1955) are epizootically important and pose an extreme danger to aquaculture.